Blood sample collection and patient identification demand improvement: a questionnaire study of preanalytical practices in hospital wards and laboratories - Wallin, Olof; Söderberg, Johan; Van Guelpen, Bethany; Stenlund, Hans; Grankvist, Kjell; Brulin, Christine (Scandinavian journal of caring sciences, 2010)
Scand J Caring Sci; 2010; 24; 581–591